Effect of carbonate apatite nanoparticles on the physicochemical properties and cytocompatibility of an experimental dental adhesive - AbdelRazik, Heba E.; Dahl, Jon E.; Kopperud, Simen E. (MJS Publishing, Medical Journals Sweden AB, 2026)
Objective: The study aimed to evaluate the effect of incorporating silanized and non-silanized carbonate apatite nanoparticles (CA5n) on the physicochemical properties and cytotoxicity of a hydrophilic experimental adhesive.
Materials and methods: A dental adhesive composed of 70% bisphenol A diglycidyl ether dimethacrylate, 28.75% 2-hydroxyethyl methacrylate, 0.25% camphorquinone, and 1% ethyl N, N-dimethyl-4-aminobenzoate was used. CA5n, synthesized with a CO₃/PO₄ molar ratio of 5, was used in both silanized and non-silanized forms at concentrations of 0.5, 1, 2 or 4% (wt). The degree of conversion (DC) was measured using Fourier Transform Infrared spectroscopy (n = 5) immediately, 5 minutes, and 60 minutes after curing. Water sorption and solubility were evaluated over 28 days (n = 6). The cytotoxicity of 24-hour and 7-day extracts (n = 6) was assessed using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay in triplicate. DC data were statistically analyzed using a mixed model. Independent-samples t-tests and Wilcoxon tests were used, depending on data normality, to analyze water sorption, solubility, and cell viability results. Statistical significance was set at p < 0.05.
Results: The addition of CA5n significantly increased the DC over time, regardless of the concentration or silanization status. All CA5n groups exhibited high water sorption and acceptable water solubility, unaffected by concentration or silanization. Water sorption increased significantly with higher CA5n concentrations compared to the control, except in the 0.5% non-silanized (NS) group. Water solubility remained below 7.5 µg/mm³ (ISO 4049 requirement), with no significant differences among groups. Cell viability decreased significantly across all experimental groups compared to the negative control, with similar effects observed in both 24-hour and 7-day extracts.
Conclusion: Adding CA5n to an experimental adhesive increased the DC and the water sorption. According to ISO 10993-5, the experimental adhesive, with and without CA5n, demonstrated low cytotoxicity potential.